2014
DOI: 10.1021/bm500872g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Chromogenic and Fluorogenic Substrates for High-Throughput Detection of Enzymes That Hydrolyze Inorganic Polyphosphate

Abstract: Inorganic polyphosphates, linear polymers of orthophosphate, occur naturally throughout biology and have many industrial applications. Their biodegradable nature makes them attractive for a multitude of uses, and it would be important to understand how polyphosphates are turned over enzymatically. Studies of inorganic polyphosphatases are, however, hampered by the lack of high-throughput methods for detecting and quantifying rates of polyphosphate degradation. We now report chromogenic and fluorogenic polyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…By quantifying the inert, signal-bearing probe that is released during P hydrolysis, these substrates can be used to track P-hydrolysis rates independently of P dynamics, which is especially important at high cell densities. Synthesis of labeled inorganic poly-P has been described (Choi et al, 2010;Hebbard et al, 2014), but these substrates were unreactive in positive controls tested in this study (data not shown).…”
Section: Synthesis and Perspectivesmentioning
confidence: 78%
“…By quantifying the inert, signal-bearing probe that is released during P hydrolysis, these substrates can be used to track P-hydrolysis rates independently of P dynamics, which is especially important at high cell densities. Synthesis of labeled inorganic poly-P has been described (Choi et al, 2010;Hebbard et al, 2014), but these substrates were unreactive in positive controls tested in this study (data not shown).…”
Section: Synthesis and Perspectivesmentioning
confidence: 78%
“…To prepare diamine-linked polyP samples 1b – 3b , polyP 12, 22, and 45 were coupled to 2,2-(ethylenedioxy)bis(ethylamine) 4 by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide-mediated (EDAC-mediated) phosphoramide coupling using a procedure modified from Hebbard et al 38 The 31 P NMR spectra of the resulting bis-phosphoramide end-capped polyP conjugates showed complete conversion to polyP-diamines 1b – 3b , as determined by the appearance of the characteristic P–N resonance at −2.0 ppm. The polyP-diamines were purified by precipitation into ethanol, rather than acetone 39 to avoid imine formation, which was identified as a side reaction with acetone.…”
Section: Resultsmentioning
confidence: 99%
“…Other in vitro substrates for NUDT2 whose levels might be affected by its loss include Ap 5 A, Ap 6 A, other homodinucleoside polyphosphates with four or more phosphoryl groups, e.g. diguanosine tetraphosphate (Gp 4 G) [ 4 , 5 ], inorganic polyphosphate [ 151 ] and phosphoribosyl pyrophosphate [ 152 ], but there is no evidence to suggest that these are significant substrates in vivo [ 4 ]. Ap 5 A and Ap 6 A appear to be confined to secretory granules in certain specialized cells while no specific mechanisms are known for the synthesis of Gp 4 G and other homodinucleoside polyphosphates in mammalian cells [ 4 , 5 ].…”
Section: Resultsmentioning
confidence: 99%